2012
DOI: 10.1159/000336171
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Changes and Protective Effect of <i>L</i>-Carnitine in Rat Kidney Ischemia/Reperfusion Injury

Abstract: Background: Although great progress has been made in the pathogenesis and treatment of acute kidney injury (AKI), it still has high incidence and poor prognosis. The present study was performed in order to further understand the metabolomic changes of ischemia/reperfusion (I/R)-induced AKI and the protective effect of L-carnitine on AKI. Methods: Kidney tissues and serum samples were collected at different time points from three groups of rats including control group, I/R group and L-carnitine-pretreated group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 63 publications
0
33
1
1
Order By: Relevance
“…Evidence shows that kidney injury and cell death can be caused during ischemic stress with depletion of ATP, activation of enzymes including phospholipases, proteases, and reactive oxygen species (ROS), generating enzymes like nitric oxide synthase that occur as early as 2 h after IR (8,15,18). Since the kidney is the major organ for excreting metabolic end products, its injury can cause changes in the renal metabolic profile, and understanding its influence on kidney function will shed light on new potential diagnostic markers and therapeutic targets in AKI (17,21,34,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that kidney injury and cell death can be caused during ischemic stress with depletion of ATP, activation of enzymes including phospholipases, proteases, and reactive oxygen species (ROS), generating enzymes like nitric oxide synthase that occur as early as 2 h after IR (8,15,18). Since the kidney is the major organ for excreting metabolic end products, its injury can cause changes in the renal metabolic profile, and understanding its influence on kidney function will shed light on new potential diagnostic markers and therapeutic targets in AKI (17,21,34,43).…”
mentioning
confidence: 99%
“…Since the kidney is the major organ for excreting metabolic end products, its injury can cause changes in the renal metabolic profile, and understanding its influence on kidney function will shed light on new potential diagnostic markers and therapeutic targets in AKI (17,21,34,43). Advances in functional genomics and proteomics have fostered progress in our understanding of the pathogenic mechanisms involved and identified some novel protein biomarkers and candidate therapeutic targets in plasma, urine, and tissues which precede changes in commonly used clinical markers of renal dysfunction like plasma creatinine (6,14,18,29,41). Comparatively little, however, is known regarding the role of lipids in pathogenic mechanisms of AKI (1,5,39).…”
mentioning
confidence: 99%
“…11,12 The importance of the free radicals in kidney disease was shown in several experimental models. [9][10][11][12][13][14] Previous studies suggested that renal IR injury increased lipid peroxidation and decreased GSH levels and activities of antioxidant enzymes in both erythrocytes and the kidney. The current study findings are also in accordance with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 Apart from its main role in energy metabolism, L-carnitine is an antioxidant that prevents the accumulation of end-products of lipid peroxidation. [9][10][11][12][13] It also exhibits powerful protective effects against different kidney injury models including IR injury, myoglobinuric acute kidney injury, and chronic renal failure. [9][10][11][12][13][14] It has been reported that L-carnitine deficiency destabilizes the erythrocyte membrane and leads to altered function of the erythrocyte sodium potassium pump with reduced erythrocyte survival time.…”
mentioning
confidence: 99%
“…La perte cellulaire par né crose et l'apoptose entraînent la desquamation des cellules é pithé liales vers la lumiè re des tubules ré naux, conduisant à l'obstruction de ces derniers. Du point de vue mé tabolomique, le pattern des mé tabolites endogè nes, é tabli par chromatographie liquide de haute performance couplé e à la spectromé trie de masse, apparaît rapidement modifié suite à une I/R ré nale [12]. Endé ans les 2 premiè res heures suivant une I/R, la teneur plasmatique et urinaire en lysophospholipides, acides gras libres et nitrotyrosines augmente, tandis que le taux de carnitine et d'acé tyl-carnitine diminue significativement.…”
Section: Physiopathologie De L'isché Mie Ré Naleunclassified